Editorial: Innovative Analysis Ecosystems for HEP Data - Sekmen, Sezen; Innocenti, Gian Michele; Jayatilaka, Bo (Frontiers in Big Data, 2021)
This editorial summarizes the contributions to the Frontiers Research topic “Innovative Analysis Ecosystems for HEP Data”, established under the Big Data and AI in High Energy Physics section and appearing under the Frontiers in Big Data and Frontiers in Artificial Intelligence journals.